Implementasi Surat Menyurat di Dinas Pertanian Tanaman Pangan dan Holtikultura - Zainarti Zainarti; Sucita Saskya Piliang (Universitas 45 Surabaya, 2024)
The implementation of correspondence at the Food Crops and Horticulture Agriculture Office is very important to ensure smooth communication between the office and other parties, both internal and external. Correspondence is used for various purposes, such as notifications, requests, submissions, and so on. In the implementation of correspondence at the Food Crops and Horticulture Agriculture Office, there are several things that need to be considered. First, the letter format must be adjusted to the applicable standards and can facilitate the archiving process. Second, the use of clear and easy-to-understand language so that the message can be conveyed properly. In addition, letter security must also be considered. Letters containing confidential or important information must be kept confidential and must not be misused. Therefore, procedures for sending, storing, and deleting letters must be well organized and carried out in accordance with applicable regulations. In practice, the implementation of correspondence at the Food Crops and Horticulture Agriculture Office can utilize information technology, such as the use of email or a mail management information system to speed up and facilitate the correspondence process. However, the use of technology must be accompanied by adequate security so as not to cause harm to the agency. By implementing correspondence properly, the Food Crops and Horticulture Agriculture Office can improve work efficiency and effectiveness and strengthen relationships with other parties, so as to achieve the goals that have been set.